Analysis Of Healthcare Employees Acceptance Of Digital Transformation In Inpatient Department Electronic Medical Record (EMR) Application At Private Hospital In Tangerang - Siagian, Ricko Sony; Tjhin , Viany Utami (International Journal of Advances in Data and Information Systems, 2025)
This study examines the acceptance of healthcare professionals toward digital transformation through the implementation of Electronic Medical Records (EMR) in the inpatient department (IPD) at a private hospital in Tangerang. The research applies a combined analytical model of the Unified Theory of Acceptance and Use of Technology 2 (UTAUT-2) and the Technology Acceptance Model (TAM). A total of 160 doctors, including specialists, formed the study population, with 115 respondents selected as samples. The findings indicate that healthcare professionals generally feel comfortable using the EMR system and have integrated it into their daily practice, although improvements in active utilization and system optimization are still required. Statistical analysis shows that Performance Expectancy, Effort Expectancy, System Quality, and Facilitating Conditions significantly influence Intention to Use, while Habit has no significant effect. Moreover, Intention to Use strongly impacts Use Behavior. These results highlight that enhancing system reliability, usability, and organizational support is essential to increase healthcare professionals’ adoption and behavioral use of EMR in the inpatient department of private hospitals in Tangerang.